1998
DOI: 10.1053/ajkd.1998.v31.pm9631837
|View full text |Cite
|
Sign up to set email alerts
|

Familial amyloid polyneuropathy type I (Portuguese): Distribution and characterization of renal amyloid deposits

Abstract: Renal amyloidosis has been considered rare and late in the evolution of the transthyretin (TTR) familial amyloid polyneuropathy (FAP) of the Portuguese type (type I). Renal biopsy has been performed systematically in 14 patients with FAP type I before liver transplantation. In all patients, TTR Met30 mutation was shown. Seven had proteinuria or abnormal microalbuminuria, whereas seven others had no urinary abnormalities. All had renal amyloid deposition predominantly in the medulla. Glomerular and vascular inv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
43
0
2

Year Published

2000
2000
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 56 publications
(47 citation statements)
references
References 16 publications
2
43
0
2
Order By: Relevance
“…In the present study we found that the severity of renal amyloid deposition does not correlate with the severity of renal impairment, which has been shown before [1,2]. However, the degree of renal impairment correlated with severity of glomerulosclerosis which is a secondary effect of amyloidosis induced renal damage.…”
Section: Discussionsupporting
confidence: 63%
“…In the present study we found that the severity of renal amyloid deposition does not correlate with the severity of renal impairment, which has been shown before [1,2]. However, the degree of renal impairment correlated with severity of glomerulosclerosis which is a secondary effect of amyloidosis induced renal damage.…”
Section: Discussionsupporting
confidence: 63%
“…Proximal tubules positively react with anti-TTR antibody inside the cells, which can be sustained by internalization of TTR by megalin (45,46). Renal dysfunction and the degree of proteinuria are correlated with heavy amyloid deposition in the glomeruli, arterioles, and medium vessels, but not with deposition in medullary tissues (42). Renal deposition does not parallel that of myelinated nerve fiber loss in the sural nerve, suggesting that evolution and severity of nephropathy are not correlated with the degree of neuropathy (21,44,47).…”
Section: Renal Pathologymentioning
confidence: 93%
“…In one report, in which half the patients studied had normoalbuminuria, amyloid was found in all cases (42). In another report, which involved only 4 patients with proteinuria, 13 of the 14 patients had amyloid deposits (36).…”
Section: Renal Pathologymentioning
confidence: 96%
“…Kidney amyloidosis is a common finding in FAP, 15,80 although renal impairment is not as common as in secondary (AA) or primary (AL) amyloidosis. However, renal insufficiency has been present in several of our transplant recipients.…”
Section: Kidney and Bladder Impairmentmentioning
confidence: 99%